Analysis of deformation and mode shape in the landing gear of light Unmanned Aerial Vehicle. (February 2020) - Das, Nikimoni; Das, Soumik; Mishra, Durgesh Kumar; Pandey, Krishna Murari
Abstract: During the landing of aircraft, the landing gear system absorbs energy through the impact of landing. Impact landing produces stress as well as deformation. The current study focuses on the numerical simulation of the landing gear system with the help of ANSYS software. Deformation is an important criterion to consider when testing a model under certain loading conditions which occurs along its span length. The majority of the deflections occur at free ends of the forks of the landing gear. The bottom plate being fixed has zero deflections in all directions. The deflections occur along the y-axis. As the impact loads were increased, the deformation increased gradually. Modal analysis has been performed to obtain the natural frequency of the model made of Aluminum Alloy Al 6061- T6. The maximum frequency was found to be 974 Hz causing a deflection of 403.59 mm. These Natural frequencies have help in calibrating the operating frequency to avoid resonance.